Health education and health promotion revisited. (October 2019) - Nutbeam, Don
Thirty years ago, the World Health Organization (WHO) Ottawa Charter for Health Promotion created a paradigm shift in addressing major public health challenges. Traditional approaches to health education focused on personal health 'risks' and lifestyle choices were quickly overshadowed by the attention given to more comprehensive policy and environmental interventions. Since that time health education has evolved in content, media use and sophistication of communication to fulfil a wider range of purposes. The concept of health literacy has been useful in sustaining this change. As the tools for communication have been transformed by digital communication, and the marketplace for communication has become more crowded and complex, health education has continued to evolve to reflect these changes, enabling people to navigate competing sources of information and to engage meaningfully with social and economic determinants of health. Equitable access to quality health education and lifelong learning remain the cornerstones of modern health promotion.